The vertex Zagreb indices of some graph operations - De, N. (Carpathian Mathematical Publications, 2016)
Recently, Tavakoli et al. introduced a new version of Zagreb indices, named as vertex Zagreb indices. In this paper explicit expressions of different graphs operations of vertex Zagreb indices are presented and also as an application, explicit formulas for vertex Zagreb indices of some chemical graphs are obtained.